Oral health education and prevention strategies among remote Aboriginal communities: a qualitative study. (22nd November 2021) - Patel, J; Durey, A; Naoum, S; Kruger, E; Slack‐Smith, L
Abstract: Background: The delivery of effective oral health promotion strategies is essential to improving oral health outcomes among remote Aboriginal communities. This study aimed to explore the perceptions and attitudes of Aboriginal Australians living in remote Kimberley communities towards oral health education and disease prevention. Methods: Semi‐structured interviews and yarning circles were carried out following purposive sampling of Aboriginal adults living in the East Kimberley region of Western Australia. Results: A total of 80 community members participated in the yarning process. School‐based oral health promotion and community‐driven restrictions on the sale of sugary food and drink were seen as positive strategies in improving oral health. Lifestyle changes brought about by modernity, internet availability and fixed community stores were perceived to create new challenges and shift the priorities for those living in remote communities. Conclusions: Community‐based yarning may better inform future oral health strategies in the Kimberley. A neoliberal approach of shifting responsibility onto the individual ignores the complex social inequities faced by Aboriginal people living in remote communities where macro‐level determinants such as remoteness, food security and education significantly influence decisions around diet and oral health.